Use of YouTube™ as a self-directed learning resource in oral surgery among undergraduate dental students: a cross-sectional descriptive study. Issue 10 (December 2019) - Aldallal, S.N.; Yates, J.M.; Ajrash, M.
Abstract: This cross-sectional descriptive study was done to assess the use and effectiveness of YouTube™ as a learning resource for oral surgery by fourth and final-year dental students at a single university. A study-specific survey was distributed to fourth (n = 83) and final-year (n = 86) dental students during a six-week period. In total, 122 (72%) responded. Most (n = 82, 67%) used YouTube™ as study material, and 50 (41%) stated that the videos had influenced their practice. Generally, the quality was rated as good, and YouTube™ was a popular and influential learning resource. However, the material was not always consistent with that of the curriculum, and students should use it with caution as there is no quality assurance with respect to educational content or learning outcomes. Institutions should provide recorded learning material and teach students skills in the critical appraisal of contemporary teaching materials such as open-resource videos.